2018
DOI: 10.1186/s13567-018-0529-7
|View full text |Cite
|
Sign up to set email alerts
|

Counting the dead to determine the source and transmission of the marine herpesvirus OsHV-1 in Crassostrea gigas

Abstract: Marine herpesviruses are responsible for epizootics in economically, ecologically and culturally significant taxa. The recent emergence of microvariants of Ostreid herpesvirus 1 (OsHV-1) in Pacific oysters Crassostrea gigas has resulted in socioeconomic losses in Europe, New Zealand and Australia however, there is no information on their origin or mode of transmission. These factors need to be understood because they influence the way the disease may be prevented and controlled. Mortality data obtained from ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 65 publications
(116 reference statements)
0
25
0
Order By: Relevance
“…Therefore, direct transmission could occur by close contact (Whittington et al . ). In fact, the higher mortality of oysters in baskets compared to oyster on ropes may be due to the direct transmission between oysters in the closer proximity within baskets (Pernet et al .…”
Section: Oshv‐1 Virus and Its Variants Associated With Oyster Mortalimentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, direct transmission could occur by close contact (Whittington et al . ). In fact, the higher mortality of oysters in baskets compared to oyster on ropes may be due to the direct transmission between oysters in the closer proximity within baskets (Pernet et al .…”
Section: Oshv‐1 Virus and Its Variants Associated With Oyster Mortalimentioning
confidence: 97%
“…The data obtained from experimental populations of C. gigas during natural epizootics of OsHV‐1 disease in Australia showed that direct transmission could have occurred at a local scale (<40 cm separation distance)(Whittington et al . ).…”
Section: Oshv‐1 Virus and Its Variants Associated With Oyster Mortalimentioning
confidence: 97%
See 2 more Smart Citations
“…by contact), dispersal in the water column (e.g. through tidal currents) is likely to play a significant role in the local spread of disease (Whittington et al 2018), especially in areas with a high density of farms in close proximity (Murray 2013, Pernet et al 2016). Furthermore, since most shellfish aquaculture operations in New Zealand are open water systems, it is reasonable to assume that an organism newly established in wild populations will eventually spread to adjacent or related farmed stocks and vice versa .…”
Section: Domestic Risk Pathwaysmentioning
confidence: 99%